Prevalence of Fungal Rhinosinusitis in Patients Presenting with Nasal Polyps - Wajih-Ud-Din Shinwari, Sadaf Raffat Mustafa, Nighat Qamer, Uzair Mushahid, Azmatullah Khan, Amjad Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To see the prevalence of fungal rhino sinusitis in patients presenting with nasal polyposis. Study design: Cross-sectional study. Place and duration of study: Department of Otorhinolaryngology and Head and Neck surgery, PIMS, Islamabad from 1st October 2021 to 31st March 2022. Methodology: Patients presenting with nasal polyps fulfilling our inclusion criterion in ENT Department in PIMS. Eighty patients presenting with nasal polyps for surgery after admitting them and the specimen was sent for fungal culture. Results: Sixty nine patients showed positive culture for fungal rhino sinusitis and only 11 patients were negative for fungal growth. Among 69 patients 51 patients were males and 18 were females. Eighty five percent male patients showed fungal growth while 90% females showed fungal growth. Conclusion: The nasal polyps is closely related to fungal infection, so all patients presenting with nasal polyps are suggested to undergo fungal culture and work-up should be done for fungal rhino sinusitis to rule fungal infection is suggested, so that early diagnosis is made and earliest treatment is started for the disease. Key words: Nasal polyps, Fungal culture, Fungal rhino sinusitis